2020
DOI: 10.1101/2020.01.29.20019547
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real-Time Estimation of the Risk of Death from Novel Coronavirus (COVID-19) Infection: Inference Using Exported Cases

Abstract: The exported cases of 2019 novel coronavirus infection that were confirmed outside of China provide an opportunity to estimate the cumulative incidence and confirmed case fatality risk (cCFR) in mainland China. Knowledge of the cCFR is critical to characterize the severity and understand the pandemic potential of COVID-19 in the early stage of the epidemic. Using the exponential growth rate of the incidence, the present study statistically estimated the cCFR and the basic reproduction number-the average numbe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
190
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 186 publications
(206 citation statements)
references
References 26 publications
13
190
0
3
Order By: Relevance
“…This study presents the estimates of epidemiological characteristics of COVID-19 infections that are key parameter for studies on incidence, case fatality, and epidemic final size, among other possibilities [7,11]. From the 95th percentile estimate of the incubation period we found that the length of quarantine should be at least 14 days, and we stress that the 17-24-day time delay from illness onset to death must be addressed when estimating COVID-19 case fatality risk.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This study presents the estimates of epidemiological characteristics of COVID-19 infections that are key parameter for studies on incidence, case fatality, and epidemic final size, among other possibilities [7,11]. From the 95th percentile estimate of the incubation period we found that the length of quarantine should be at least 14 days, and we stress that the 17-24-day time delay from illness onset to death must be addressed when estimating COVID-19 case fatality risk.…”
Section: Discussionmentioning
confidence: 93%
“…Here, r is the exponential growth rate (estimated at 0.14 [11]), T is the latest time of observation (31 January 2020), and F(.) is the cumulative density function of f (.…”
Section: Statistical Modelmentioning
confidence: 99%
“…What the estimate of 9.2% also indicates is that the cCFR value is likely 11 times greater than the risk of death among all infected individuals, which is referred to as the infection fatality risk (IFR) [9]. For instance, if the value of cCFR is 5-8% as estimated earlier in [5], the IFR can be in a range of 0.5-0.7% out of all infected individuals. This value is also in line with another estimate of the IFR at 0.8% (95% CI: 0.4, 3.0) [6].…”
Section: Infection Fatality Risk (Ifr): All Infected Individuals As Tmentioning
confidence: 98%
“…where c t is the daily number of cases (i.e., incidence) and f s is the probability density function of the time from illness onset to death-the relative frequency of the time from illness onset to death among fatal cases. See Jung et al [5] as an example of application of (2) for the ongoing COVID-19 epidemic. Table 1 compares the cCFR (adjusted estimate) and the value resulting from simple division (not adjusting for the time from illness onset to death).…”
Section: Graduating From Simple Divisionmentioning
confidence: 99%
See 1 more Smart Citation